The role of psychological empowerment on job satisfaction among Malaysian public sector workers - Ma'rof, Aini Azeqa; Mohd Fadzilan, Danial Aiman; Hamsan, Hanina H. (Human Resource Management Academic Research Society, 2021)
A number of recent research studies have demonstrated the presence of a positive association between working environment and psychological factors on work satisfaction. Therefore, this study aimed at determining the relationships between workplace friendship, psychological empowerment and organizational commitment on job satisfaction among public sector workers. A total of 356 employees participated in this study where results revealed that the majority of the employees have a high level of workplace friendship, psychological empowerment, organizational commitment and job satisfaction. Besides, workplace friendship and psychological empowerment showed a significant relationship with job satisfaction, meanwhile, no significant relationship between organizational commitment and job satisfaction was shown. Moreover, psychological empowerment has been identified to be the unique predictor that leads to job satisfaction among employees. Findings of this study suggested that psychological training and programs might be effective and crucial to be regularly implemented in order to boost employees’ motivations and job satisfaction that later benefits the organization. The theoretical impact and suggested intervention will be discussed in detail.